The Effectiveness of the Direct Learning Model in Improving Vocational Skills in Making Flowers from Onion Skins for Children with light mental retardation - Indri Ansih; Zulmiyetri Zulmiyetri (EDUCATIO : Journal of Education, 2016)
The background of the problem in this study is to see the vocational ability to make flowers from onion skins for light mental retardation children in SLB Perwari Padang. The problem found was that the child had not been able to make flowers from onion skins that had never before been taught to children. The purpose of this study is to prove whether the direct learning model can improve the vocational ability to make flowers from onion skins for light grade VIII C children in Perwari Padang SLB. This type of research is an experimental research that is by using quasi-experimental or also called quasi-experiment with a single group design that is Onegrup pretest-posttest Design, with research subjects of five light mental retardationchildren. The abilities assessed by pretest and posttest were processed and compared using the Wilcoxon Sign Rank Test. So it can be concluded that the direct learning model is effective in improving the vocational skills of making flowers from onion skins for light retardation in Perwari Padang SLB. The results of this study could be taken into consideration for teachers to be able to use direct learning models in improving children's vocational skills, especially in teaching how to make flowers from onion skins.